In-vitro evaluations of Trichoderma spp. against Different Diseases of Pigeonpea in Nagaland - Chang, Betikundang; Ao, N. Tiameren; Sumi, Kavi; Pongener, Narola; Neog, Pankaj (International Journal of Economic Plants, 2023)
The investigation was carried out at the laboratory of Plant Pathology Department, SASRD, Nagaland University (NU), Medziphema Campus, Nagaland, India during the year kharif (August-October, 2020) to evaluate the antagonistic potentiality of Trichoderma spp. (T. harzianum, T. asperellum and T. virens) against three diseases of pigeonpea viz. Alternaria leaf spot (Alternaria alternata), Collar rot (Sclerotium rolfsii), Phytophthora blight (Phytophthora drechsleri f. sp. cajani). Dual culture technique was followed to test the efficacy of these antagonists as bio-agents against the pathogens. Result of in vitro screening test revealed that all the bio-agents significantly inhibited the mycelial growth of the pathogens. Among the three Trichoderma spp. evaluated, T. harzianum (55.53%) was found to be the highest in per cent inhibition of A. alternata, T. asperellum (50.87 %) recorded highest per cent inhibition on S. rolfsii and T. virens (55.88%) recorded highest per cent inhibition on Phytophthora drechsleri f. sp. cajani. Thus, the in vitro study suggests that the Trichoderma spp. has a potential to be used as bio-agents in managing these three fungal diseases viz. Alternaria leaf spot, Collar rot and Phytophthora blight of pigeonpea.